Level of service analysis of selected walkways corridors in Johor Bahru - Balarabe, Abubakar Sadeeq (2016)
Most individual trips whatever the primary mode used, begin or finish with a walk section; so walking is fundamental component of all travel. Walking behaviour and pedestrian flow characteristics lay the foundation for the planning and design of pedestrian facilities. Therefore the needs to access pedestrian facilities should be considered in the design of transportation facilities. Pedestrian facilities includes sidewalks, paths, crosswalks, stairways, curbs cuts and ramps, and transit stops. Accurate estimation of these facilities should be conducted so as to reduce congestion and promote walkability in central business district (CBD) for a sustainable society. However conventional ways of assessment are flawed, new approaches must be constantly investigated to improve on the current estimation methods. The study evaluates the walkways and crosswalks in the city square of Johor Bahru. Video graphic survey methods was used for pedestrian counts, having advantage over the manual method. Flow, speed, density and effective width of the walkway were the variables measured. Some on the positions identified, others back in the lab or office after extracting the data from the video. Hand tape, masking tape, stop watch and video camera/ tripod stand were the tools/apparatus used on various positions for collecting data. The flow rate calculated, in conjunct ion with HCM were used to estimate PLOS. Regression analysis was conducted on the flaws identified so as to improve on the current method of estimation